2021
DOI: 10.1016/j.jbc.2021.100458
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-saturated calmodulin binds tightly to the N-terminal domain of A-type fibroblast growth factor homologous factors

Abstract: Edited by Karen FlemingVoltage-gated sodium channels (Na v s) are tightly regulated by multiple conserved auxiliary proteins, including the four fibroblast growth factor homologous factors (FGFs), which bind the Na v EF-hand like domain (EFL), and calmodulin (CaM), a multifunctional messenger protein that binds the Na V IQ motif. The EFL domain and IQ motif are contiguous regions of Na V cytosolic C-terminal domains (CTD), placing CaM and FGF in close proximity. However, whether the FGFs and CaM act independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 109 publications
(195 reference statements)
1
8
0
Order By: Relevance
“…Its primary sequence is identical across all vertebrates [ 2 ] and comprises two domains connected by a linker ( Figure 1 ). How CaM maintains binding selectivity towards its targets with affinities ( ) varying from nM [ 3 ] to μM [ 4 ] has been studied for decades [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. These studies have generated valuable insights into factors contributing to its binding selectivity, which includes hydrophobic residues in targets that interact with CaM, CaM’s conformational heterogeneity at the binding surface, and its Ca -binding sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Its primary sequence is identical across all vertebrates [ 2 ] and comprises two domains connected by a linker ( Figure 1 ). How CaM maintains binding selectivity towards its targets with affinities ( ) varying from nM [ 3 ] to μM [ 4 ] has been studied for decades [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. These studies have generated valuable insights into factors contributing to its binding selectivity, which includes hydrophobic residues in targets that interact with CaM, CaM’s conformational heterogeneity at the binding surface, and its Ca -binding sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although an indirect interaction between Na V -associated FGF and CaM has been suggested for Na V 1.4, direct interaction and potential stoichiometry have not been explored until the Shea laboratory's extraordinary attention to detail brought the molecular mechanism into focus ( 6 , 7 , 8 ). The group has a strong history of bringing molecular studies to relevant physiological questions, including notably their description of the cooperativity of Ca 2+ binding by CaM, of import to CaM’s extensive substrates.…”
mentioning
confidence: 99%
“…Mahling et al. have now demonstrated that the Na V complex has multiple CaM-binding sites with differing calcium-saturating preferences, accentuating the nuanced and extremely dynamic nature of the interactions ( 6 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations